THE EMBODIMENT OF LEGALITY PRINCIPLES IN HUMILIATION CRIMINAL OFFENSE - Ilyas, Amir (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed to find out the embodiment of the legality principles of criminal law both the provisions in the Criminal Code (KUHP) and those in the Information and Electronic Transaction Law (UUITE). It uses normative-juridical research with primary legal materials (laws and verdicts of the constitutional court) and secondary legal material (literature on insult criminal law). An analysis legal material is performed by qualitative analysis, describing vague legal norms, then performing legal interpretation and conceptualization. The results showed that the provisions of humiliation criminal offense both contained in KUHP and UUITE did not meet the principle of legality, there are still provisions of humiliation criminal offense whose elements of criminal offenses are vague, such as in the kinds of humiliation: defamation, accusation with slander, humiliating people those who have died, and humiliation through ITE means. In this paper examine the criminal law of humiliation in KUHP and UUITE in terms of the embodiment of the principle of legality, namely in the classification of the third and fourth part. Whereas in the enforcement of criminal law that must protect human rights, if there are unclear provisions, multi-interpretations, it is certainly impossible to realize.